Neurocognitive Functioning And Interpersonal Difficulties In Diabetic Mellitus Type II Patients - Rashid, Nazish; Bashir, Umaiza (Journal of Rawalpindi Medical College, 2023)
Objectives: To determine the level of Neurocognitive Functioning, and Interpersonal difficulties in People with Diabetes Mellitus type II. Material and Method: A purposive sampling strategy was used. A sample (N=100) with age range (40-60) years was taken in the study, in which 46% Men or 54% Women Diabetes Mellitus type II patients were included. The research design was cross-sectional. Neuro-Cognitive Assessment Battery and Interpersonal Relationship Scale for Diabetic Patients were used. Results: Pearson Correlation analysis results showed that there was a positive significant relationship between neurocognitive functioning and interpersonal difficulties. Hierarchal Regression analysis showed education level was a predictor of interpersonal difficulties in diabetic mellitus type II patients with poor neurocognitive functioning. Limitations and suggestions are discussed. Keywords: Neurocognitive functioning, Interpersonal Difficulties, Diabetic Mellitus Type II